PROBLEMY I CELE ROZWOJOWE MIAST POLSKI - Kotus, Jacek (Wydział Prawa i Administracji UAM, 2002)
This paper aims at presenting the main developmental problems and priorities o f Polish cities at the turn of the epoch. The research has been founded upon an analysis of approximately 100 development strategies of selected cities. Both the developmental problems and objectives of Polish cities have been presented in the following four spheres: (i) society and culture, (ii) economy and infrastructure, (iii) nature and environment, and (iv) urban and land development. Generally, the defined difficulties present Polish cities as the focal points of particularly difficult and multifaceted developmental problems. The answer to crucial urban life inconveniences recognised through research is developmental priorities articulated in a responsible and complementary way in response to the discovered problems. The main problematic issues as well as the objectives of Polish urban organisms are universal and independent of the size of a city. The main problems in the four selected spheres result from the bad condition of the following areas: education, waste water management, waste management, roads and transport. The chief development priorities are to improve education, develop waste water management, create an efficient waste management system, modernize and develop the city transport systems.
DEVELOPMENTAL PROBLEMS AND OBJECTIVES OF POLISH CITIES